DEVELOPING LOGICAL THINKING THROUGH TEACHING ELEMENTS OF COMBINATORICS IN PRIMARY SCHOOL MATHEMATICS LESSONS - O‘rinboyev Zokir Mavlonovich (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. Today, one of the most important tasks of the educational process is to develop students’ independent and logical thinking skills. This is especially significant in primary school mathematics lessons, as it lays the foundation for successful learning at later stages.